An enchantment of ravens ebook - Rogerson, Margaret (2017)
* Instant New York Times bestseller * A Parents' Choice Silver Honor Winner * "A funny, action-packed, and sweet romance." — School Library Journal (starred review) "A phenomenal read." — RT Book Reviews A skilled painter must stand up to the ancient power of the faerie courts—even as she falls in love with a faerie prince—in this gorgeous bestseller that's "an ideal pick for fans of Holly Black, Maggie Stiefvater, and Laini Taylor" ( Publishers Weekly , starred review). Isobel is an artistic prodigy with a dangerous set of clients: the sinister fair folk, immortal creatures who cannot bake bread or put a pen to paper without crumbling to dust. They crave human Craft with a terrible thirst, and Isobel's paintings are highly prized. But when she receives her first royal patron—Rook, the autumn prince—she makes a terrible mistake. She paints mortal sorrow in his eyes—a weakness that could cost him his life. Furious, Rook spirits her away to his kingdom to stand trial for her crime. But something is seriously wrong in his world, and they are attacked from every side. With Isobel and Rook depending on each other for survival, their alliance blossoms into trust, then love—and that love violates the fair folks' ruthless laws. Now both of their lives are forfeit, unless Isobel can use her skill as an artist to fight the fairy courts. Because secretly, her Craft represents a threat the fair folk have never faced in all the millennia of their unchanging lives: for the first time, her portraits have the power to make them feel.